PENANGGULANGAN DAN PENCEGAHAN TERHADAP TINDAKAN KEKERASAN SEKSUAL YANG TERJADI DI DESA MEDAN KRIO KECAMATAN SUNGGAL - Nur Muniifah; Arie Kartika; Muhammad Yasin Ali Gea; Nadilah Agustia Nasution; M.Zulkarnain Lubis; Josias Daniel Hamonangan Sitinjak (Ekasakti Jurnal Penelitian dan Pengabdian)
Understanding the idea of prevention and countermeasures of sexual violence is the goal of this community service project Medan Krio Village area. This activity began by emphasizing the importance of knowledge related to sexual violence and problems that potentially arise due to public misunderstanding of the forms of sexual violence stipulated in law No. 12 Of 2022 On The Crime Of Sexual Violence. The implementation method includes planning activities involving 30 (thirty) participants in the Medan Krio Village Hall by providing understanding through material presented in a concise information chart and accompanied by discussion sessions. Participation in this community service project leads to a significant increase in participants ' understanding before and after participating in the activities. This fact shows that individuals who take part in this effort can benefit from later implementing their understanding in the lives of the Medan Krio Village community, in order to minimize and be free of sexual violence violations. And can carry out the implementation of the law and the purpose of punishment (rehabilitative) for the perpetrators so that the people of Medan Krio are born with character and are legally aware.